Research progress of the immunosuppressive tumor microenvironment in multiple myeloma - Yue WANG; Peng LIU (Zhongguo Linchuang Yixue)
Multiple myeloma (MM) is a hematological malignancy originating from the immune system, and the immune microenvironment plays a pivotal role in its pathogenesis and progression. The immune microenvironment not only mediates immune surveillance and response but also contributes to myeloma immune escape and target organ damage. Immune dysregulation persists throughout the disease course of MM, facilitating disease progression by conferring survival advantages to tumor cells and promoting immune editing. The interplay among various immune cell populations represents a critical factor in the exacerbation of the malignant biological behavior of myeloma cells. A comprehensive understanding of the mechanisms underlying the interaction between myeloma cells and the microenvironment, as well as their contribution to immune dysregulation and downstream effects, is essential for improving patient therapeutic strategies and prognosis. This paper aims to systematically review the literature on immune cells promoting the formation of an inhibitory MM microenvironment, thereby elucidating the current status of immune escape mechanisms in MM and exploring potential future directions of immunotherapy.